Pelaksanaan Peraturan Desa Nomor 03 Tahun 2023 Tentang Perubahan Anggaran Pendapatan Dan Belanja Desa Pamijen Tahun Anggaran 2023 Kecamatan Sokaraja Kabupaten Banyumas - Afrina Mayang; Wahyu Hariadi; Haris Kusumawardana; Esti Ningrum (Wijayakusuma Law Review, 2024)
Abstract The village as the smallest governmental entity, plays a crucial role in regional autonomy, with the readiness of the village in establishing its governance system impacting the development anda welfare of its community. The management of village finances, especially the Village Revenue and Expenditure Budget (APBDes), is crucial in supporting village development. This research aims to understand how the implementation of Pamijen Village Regulation Number 03 of 2023 concerning the Amendment of the Pamijen Village Revenue and Expenditure Budget for the Fiscal Year 2023 in Sokaraja Subdistrict, Banyumas District, and to identify the challenges faced in the implementation of Pamijen Village Regulation Number 03 of 2023 concerning the Amendment of the Pamijen Village Revenue and Expenditure Budget for the Fiscal Year 2023 in sokaraja Subdistict, Banyumas District. The methodological approach used is normative juridical with descriptive analysis. Date were obtained from field studies at the Pamijen Village Office and trough interviews with villagr officials. The research findings indicate that the implementation of APBDes in Pamijen Village complies with applicable regulations. However, there are technical constraints and budget changes that affect activity realization. It is recommended that the village government continue to evaluate and minimize constraints in the implementation of APBDes. This research is expected to contribute to the development of knowledge, particularly in the context of village financial management Keywords: Implementation, Village Regulation, APBDes Abstrak Desa sebagai entitas pemerintahan terkecil memilikiperan penting dalam otonomi daerah, dengan kesiapan desa dalam membangun system pemerintahannya berdampak pada pembangunan dan kesejahteraan masyarakatnya. Pengelolaan keuangan desa, terutama Anggaran Pendapatan dan Belanja Desa (APBDes) menjadi krusial dalam mendukung pembangunan desa. Penelitian ini bertujuan untuk mengetahui bagaimana Pelaksanaan Peraturan Desa Pamijen Nomor 03 Tahun 2023 tentang Perubahan Anggaran Pendapatan dan Belanja Desa Pamijen Tahun Anggaran 2023 Kecamatan Sokaraja Kabupaten Banyumas dan untuk mengetahui kendala yang dihadapi dalam Pelaksanaan Peraturan Desa Desa Pamijen Nomor 03 Tahun 2023 tentang Perubahan Anggaran Pendapatan dan Belanja Desa Pamijen Tahun Anggaran 2023 Kecamatan Sokaraja Kabupaten Banyumas. Metode pendekatan yang digunakan adalah yuridis normatif dengan analisis deskriptif. Data diperoleh dari studi lapangan di Kantor Desa Pamijen dan melalui wawancara dengan perangkat desa. Hasil penelitian menunjukkan bahwa pelaksanaan APBDes di Desa Pamijen sesuai dengan peraturan yang berlaku. Namun, terdapat kendala teknis dan perubahan anggaram yang memengaruhi realisasi kegiatan. Disarankan agar pemerintah desa terus melakukan evaluasi dan meminimalisie kendala dalam pelaksanaan APBDes. Penelitian ini diharapkan memberikan kontribusi dalam pengembangan ilmu pengetahuan, khususnya dalam konteks pengelolaan keuangan desa. Kata kunci : Pelaksanaan, Peraturan Desa, APBDes